2022
DOI: 10.35848/1347-4065/ac85f9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of LF-microwave hybrid plasma treatment on radish seed germination and sprout growth

Abstract: The atmospheric pressure non-thermal plasma generated by low-frequency (LF)-microwave hybrid discharge has been employed to investigate the effects of plasma treatment on the germination and growth of radish (Raphanus sativus L.) sprout seeds. The plasma generated with admixture discharge gas of Ar-O2 was adopted for the irradiation of seeds. SEM and EDX analyses were performed to elucidate the physical and chemical state changes of seed surfaces after plasma treatment. The reactive species produced in the pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…Typically, seeds are hydrophobic by nature. When seeds are exposed to CAPP for a certain period of time, reactive species (RONS) present in the CAPP may be implicated in the surface etching of the seed coat, which enhances the roughness of the seeds and causes them to become more granular, as reported by several researchers using SEM micrographs [37,54,55]. When the reactive species interact with the seed coat, they may result in the etching of a waxy layer from the surface of the seed coat (testa).…”
Section: Estimation Of Mass Loss and Water Uptake Capacity Ofmentioning
confidence: 99%
“…Typically, seeds are hydrophobic by nature. When seeds are exposed to CAPP for a certain period of time, reactive species (RONS) present in the CAPP may be implicated in the surface etching of the seed coat, which enhances the roughness of the seeds and causes them to become more granular, as reported by several researchers using SEM micrographs [37,54,55]. When the reactive species interact with the seed coat, they may result in the etching of a waxy layer from the surface of the seed coat (testa).…”
Section: Estimation Of Mass Loss and Water Uptake Capacity Ofmentioning
confidence: 99%
“…[21][22][23][24][25][26] Atmospheric pressure non-thermal plasma, considered by its highly energetic electrons, generates sufficient reactive species without inducing thermal damage to the treated surfaces. [27][28][29][30][31] These reactive species play a crucial role in mitigating pathogenic contamination and stimulating plant growth. In a previous study, we introduced a novel atmospheric pressure non-thermal plasma source known as LF-microwave hybrid plasma (LFMHP).…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, we introduced a novel atmospheric pressure non-thermal plasma source known as LF-microwave hybrid plasma (LFMHP). [28][29][30][31] This hybrid plasma combines a low-frequency (LF) plasma jet (PJ) combined with a source of microwave plasma, resulting in an expanded plasma discharge. Compared to conventional LF-PJ, the LFMHP exhibits a higher concentration of reactive species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the promotion of crop growth, biomass yield, branching, seed ripening, and better disease resistance, the use of cold plasma has beneficial effects on seed disinfection and sprouting [18]. Tonmitr et al exposed seedlings to admixture discharge gas of Ar-O 2 and showed that the LF microwave hybrid plasma produced more reactive oxygen species than a traditional LF plasma jet [19]. According to analysis using SEM, the wettability of the radish seed was modified by etching effects on the seed coat that followed the argon plasma treatments [20].…”
Section: Introductionmentioning
confidence: 99%